Perilaku Konsumen Islam Modern Perspektif Konsumsi dalam Islam (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
This study aims to determine the concept of consumption in the view of Al-Ghazali and Muhammad Abdul Mannan on its relevance to the consumption behavior of modern Muslim society. This type of research is library research using a quantitative approach method based on secondary in the form of books and related scientific journals in accordance with the theme of this research and primary data in the form of books from Al-Ghazali and Abdul Mannan. From the results of the study, it can be concluded that according to Al-Ghazali and Abdul Mannan Islamic provisions regarding consumption are controlled by five principles, namely justice, cleanliness principles, simplicity principles, generosity principles, and moral principles and there is a relevance between Al-Ghazali and Abdul Mannan's consumption concepts with The consumption pattern of modern Muslim society in Indonesia today is due to the awareness of modern Muslim society about the cleanliness of food consumption and simplicity in consumption. Modern Muslim society is more careful in terms of consumption health and avoids wasteful behavior in consuming things that are not really needed or are not primary needs